A Literary Review of Shad Kriyakala: A Novel Concept for Preventive Aspect of Health - Upadhyaya, Nilkanth (Haimaprabha, 2025)
Ayurveda, the science of life, is the most ancient medical doctrine of human civilization. Shad Kriyakala is unique concept of Ayurveda. It is also known as Chikitsavasara Kala and it explain the the stages of diseases manifestation as well as time of treatment or opportunity in the process of diseases manifestation in consecutive stages in details.It is the narration in sequential order of the abnormalities occurring in the Doshas, Dushyas, Agni and Srotasetc.Acharya Sushruta has narrated details idea of Shad Kriyakala on the subject of Varnaprashnadhyaya, Sushruta explain the incidence of Varnas in terms of Doshic disturbances. Kriya Kala occurs in six stages - Sanchaya, Prakopa, Prasara, Sthana Samshraya, Vyakti and Bheda.By knowing the concept of Shad Kriyakala physician can be able to prevent the formation of disease in initial stages, early diagnosis and prognosis of diseases and gives an idea to stop the disease formation. The Dosha when controlled in Sanchaya stage cannot go further into the consequent stages as Prakopa, Prasara etc. Thus, by knowing the concept of Shad Kriyakala, physicians have better chance and idea for the treatment of diseases and for adopting preventive and curative measures of diseases.